Mineralogy for petrologists optics, chemistry and occurrences of rock-forming minerals - Demange, Michel (CRC Press, 2012)
"This book provides a categorized and visualized overview and presents microscopic observations, systematic mineralogy, chemistry, geology, stability, paragenesis, occurrence and use in petrology of 137 minerals. Structural formula calculations are included in the appendix. Consists of a set of book and CD-ROM for students and practically-oriented researchers and professionals in geology, geological, mining, and mineral resources engineering who need a reference of mineralogy, applied to petrology.The CD-ROM contains 384 color plates with mineral microscopic visuals under various circumstances"-- Provided by publisher.
"Fluid and melt inclusions in rock-forming minerals (pp. 44-49) by Jacques Touret, Ecole de Mines Paris, France."
"A Balkema book."
Keywords: Petrology.; Minerals.; elektronické knihy; electronic books